Publishing Marine Geospatial Data on the Web: the DFO GeoBrowser - Vachon, Don; Poulin, Michel; Lafond, Pierre; Evangelatos, Timothy V. (The International Hydrographic Review, 2004)
In response to a need to integrate geospatial data from multiple locations and products, the Department of Fisheries and Oceans developed the DFO GeoPortal as a suite of standards-based geospatial services and applications. While initially implemented to support internal operations and decision-making processes, the GeoPortal was extended to support public access through the development of a new component, the GeoBrowser. This paper provides an overview of the GeoBrowser, its contents, evolution from the internal DFO GeoPortal intranet Web mapping services and shows how DFO is using it to help other stakeholders to make their data available through the Web.